CERAI GUGAT PERSPEKTIF PERUNDANG-UNDANGAN DI INDONESIA (Studi Kasus Di Pengadilan Agama Kelas 1B Watampone Pada Tahun 2010-2012) - lia, Darliana (Pasca Sarjana STAIN Watampone, 2016)
The results show that the divorce to suein the Religious Class 1B Watamponefrom year to year has increasedsignificantly, the events of divorce suegreater in number than the divorce onthe grounds that the wife is more awareof their rights and obligations inmarriage. Factors that lead to divorcecontested in the Religious are factorsmoral, Hurting, child marriage, disputecontinuously, biological defect and noharmony, these factors are supported bya state of